Inferior Vena Cava Anomalies and Pathologies - Poojary Shweta Raviraj; Venkataswamy Chandana; Hagalahalli Nagarajegowda Pradeep; Chakenahalli Puttaraj Nanjaraj (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Wide array of anatomical variations and pathologies affect the inferior vena cava (IVC). Multidetector computed tomography remains the most important modality to diagnose and evaluate the extent of involvement. The congenital variations such as duplication, anomalous course of renal veins, azygos continuation of IVC, etc., remain clinically indolent and are detected incidentally in abdominal imaging. This article describes the various congenital variants which include abnormalities in drainage, failure of development, and regression of the IVC. This article also highlights the important pathological conditions such as Budd-Chiari syndrome, primary and secondary neoplasms of the IVC, bland thrombosis, and retrograde opacification of the IVC.